AA-Amyloidosis in the Eurasian stone-curlew (Burhinus oedicnemus) - Lucía Marrero-Ponce; Cristian M. Suárez-Santana; Óscar Quesada-Canales; Natsumi Kobayashi; Candela Rivero-Herrera; Lucía Caballero-Hernández; Tomoaki Murakami; Antonio Fernández (PLoS ONE, 2025)
Amyloidosis is a group of protein misfolding diseases and a well-recognized disorder in avian species. However, the knowledge of wild avian amyloid proteome is scarce. We report here gross, histopathological, ultrastructural, immunohistochemical and proteomic findings of systemic amyloidosis in seven Eurasian stone-curlews (Burhinus oedicnemus) necropsied in the Canary Islands. Spleen (5/6–83.33%), liver (3/5–60%), kidney (3/5–60%), proventricle (3/5–60%) and intestine (3/6–50%) were the more severely affected organs. All cases underwent chronic inflammatory processes associated to helminth, bacteria or fungi infection. Verminous chronic ventriculitis was the most frequent associated pathology in 5/7 (71.43%) followed by bumblefoot in 2/7 (28.57%) cases. Electron microscopy revealed a predominantly amorphous substance with 10 nm diameter non-branching amyloid fibrils. AA amyloidosis was characterized by immunohistochemistry and mass spectrometry analysis. By mass spectrometry three amyloid signature proteins were also identified: vitronectin, apolipoprotein A-IV and apolipoprotein A-I in 6/7 (85.71%), 4/7 (57.14%), and 3/7 (42.86%) cases, respectively, contributing with new knowledge about the amyloid proteome of amyloidosis in wild avian species.